Modelagem do sequenciamento da ensilagem em processos industriais de formação de receitas - Thiago Henrique Nogueira (2008)
The current work is the result of a real case analysis of production lot and sequencing procedure, in the cement industry, aiming to reduce production line stop time. The cement fabrication process is a continuous process, such that can be analyzed as a single equipmentreceiving raw material, processing into nished goods. The motivation for this work was the state of disorganization of the factory, resulting on rates of 5 percent of back ordering and 20 percent of unproductive time. The goal of this project is to increase productive time, reducing back ordering through a better lot dimensioning and scheduling. The scheduling process includes penalties for production delay or anticipation and includes a method of sequencing that considers the setup time between the dierent products. The lot size denition process also includes penalties for stock-out situations and for stock maintenance costs, always considering production capacity restrictions over a period.The model and the method proposed proved to be capable of promoting a higher degree of organization on the production line. Nevertheless, in face of real life uncertainties, the time required to nd the optimum solution is incompatible with production fast decision requirements, making necessary the development of alternative methods with faster response time, without losing quality.